METHODS FOR DEVELOPING STUDENTS’ PRACTICAL TASK PERFORMANCE SKILLS USING METAL TOOLS AND EQUIPMENT (Eureka Journal of Education & Learning Technologies, 2026)
This article explains the implementation of practical tasks based on technologies for using various types of metals, modern sewing machines, machine tools, and other equipment in order to teach subjects of technological education to students in an engaging and high-quality manner. Furthermore, the article highlights the importance of intensively increasing students’ interest in technological education subjects, developing their creative ideas, creative thinking, imagination in using metals and technical devices made from them during product manufacturing, and improving their skills in independent work and performing practical tasks using innovative teaching methods.
Keywords: Metal, lesson, practical, task, independent, education, tool, equipment, technique, technology.